KONSTRUKSI REALITAS PEMBERITAAN WACANA SYIAH PADA MEDIA ONLINE ORMAS SYIAH INDONESIA - Ahmad Fahrur Rozi; Ade Solihat (Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2024)
Abstract This research aims to analyze the construction of Shia discourse published in the official online media of Indonesian Shia mass organizations and how Shia media can survive amidst the siege of Sunni mainstream media in Indonesia. This research stems from the background of Shiites as a minority in Indonesia and the massive anti-Shia propaganda campaign created by sunni conservative groups. This is a qualitative research using content analysis methodology. This article used Ibn Hamad's media and reality construction theory and Erving Goffman's stigma theory. Using these theories the author found; first, referring to media and reality construction theory, it was found that the construction of Shia discourse in Indonesian Shia online media tends to display the language symbols of